Az erdélyi magyar orvosképzés II. rész Marosvásárhely - Péterffy, Árpád; Péterffy, Pál (Gerundium, 2018)
Hungarian Medical Training in Transylvania (II): Marosvásárhely. As a continuation of the study on the history of the Hungarian medical education in Cluj (Kolozsvár) that was published earlier in our journal, in this writing, the authors elaborate the history of the Institution of Medicine and Pharmacy of Târgu Mureș (Marosvásárhely), that was established in 1945, and later became a University in 1991. The study is supplemented by biographies of the rectors of the university, expressively with a special emphasis on the presentation of the activities of the rectors who had Hungarian language as a mother tongue.